Criminal responsibility for experimenting with the drug - Benbrahim, Dalila (Journal of Human Sciences, 2023)
The rapid scientific developments that the world is witnessing, especially in recent times, imposed on the specialists the necessity of experimenting with the drug, so it was necessary for the Algerian legislator, similar to the rest of the comparative legislation, to impose a number of conditions on both the one who experimented with the drug and the one subject to his experiment, and whose violation entails the establishment of criminal liability.